Numerical modelling verification of temperature distribution in ColdArc welding of thin plate - Sabdin, SD.; Hussein, NIS.; Sued, MK.; HP Manurung, Yupiter; Fadzil Jamaluddin, Mohd (International Journal of Engineering and Technology, 2018)
This study investigated, Gas Metal Arc Welding of cold rolled steel plates by Cold Arc technology. The numerical modelling analysis of temperature in lap joint of two thin plates dissimilar size plates is performed with the Marcs software. The main objective from this simulation is to identify the temperature distribution in order to execute heat inputs into finite element thermal simulation of the thin plate lap joint. The analysis comprises a finite element of model for the thermal welding simulation. Moreover, the analysis includes a moving of heat source, the deposit of the materials, the temperature dependent on material properties, the condition of the boundaries as well as the melting temperature. The effects from the distribution of the heat source with the input from the energy were further examined. Additionally, the study expands the scope to the speed of the welding according to the variety of the temperatures. Therefore, predictions on reduction of welding heat input have become critically importance. Predicted by the FEM, it is demonstrated that the temperature distribution method be able to efficiently predict the welding deformation using double ellipsoidal heat source in the thin plate lap joint.Â Â Â